The Influence of Perceptions and Knowledge About Taxation on Students' Interest in Working in The Field of Taxation (Case Study on Accounting Study Program, Faculty of Economics and Business At Universitas Kristen Indonesia) - Fitrimawati Ndruru,; Juaniva Sidharta, (Jurnal Mutiara Ilmu Akuntansi, 2025)
This research aims to determine the influence of perceptions and knowledge about taxation on students' interest in working in the field of taxation. This type of research is mixed research. The population of this research is Accounting students at the Indonesian Christian University. The method used in this research is purposive sampling for quantitative and snowball sampling for qualitative with specified criteria, namely students who have taken a specialization in taxation. The theory used in this research is the Theory of Planned Behavior (TPB). This research was processed using SPSS with the multiple linear regression method and in analyzing the data this research used descriptive statistics, data quality testing, classical assumption testing, and also hypothesis testing. The results of this research show that the variables of perception and knowledge about taxation have a positive and significant effect on students' interest in working in the field of taxation.